Microplastic-associated trophic transfer of benzo(k)fluoranthene in a limnic food web: effects in two freshwater invertebrates (Daphnia magna, Chironomus riparius) and zebrafish (Danio rerio) - Hanslik, Lisa; Sommer, Carmen; Huppertsberg, Sven; Dittmar, Stefan; Knepper, Thomas P.; Braunbeck, Thomas (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2020)
The continuously growing plastic production and incomplete recycling processes open manifold entry routes for microplastic particles (MPs) into the environment. Since knowledge on trophic transfer of contaminants sorbed to MPs is still insufficient for freshwater systems, the transfer of the model pollutant benzo(k)fluoranthene (BkF) sorbed to polymethyl methacrylate (PMMA) particles in a limnic food web was investigated: Two freshwater invertebrates (Daphnia magna and Chironomus riparius larvae) were selected and either left untreated, exposed to pristine PMMA, PMMA-associated BkF, or exposed to dissolved BkF (BkFaq). As second-level consumers, zebrafish (Danio rerio) were fed twice daily with pre-treated invertebrates over two days. Induction of hepatic cytochrome P450 by BkF was determined as 7-ethoxy-O-resorufin deethylase (EROD) activity. Both invertebrate species readily ingested PMMA particles, tracked via fluorescence microscopy and accumulated BkFaq, measured via GC-MS. Fluorescence signals in gastrointestinal tracts of zebrafish were quantified with confocal laser scanning microscopy (CLSM). The fluorescence signal in gastrointestinal tracts of zebrafish was not altered, whereas, EROD activity was significantly induced when zebrafish were fed with Chironomus riparius, pre-exposed to BkFaq. Trophic exposure scenarios with BkF sorbed to PMMA did not result in any alterations of investigated endpoints in both invertebrate species and zebrafish compared to controls. Given that BkF amounts were in the low ng-range, as detected by GC-MS, the transport of MP-sorbed BkF to zebrafish was less effective than direct exposure to waterborne BkFaq, and the potential threat of trophic transfer of substances such as BkF in limnic food webs may have been overestimated.